Deaths related to pulmonary embolism and cardiovascular events before and during the 2020 COVID-19 pandemic: An epidemiological analysis of data from an Italian high-risk area. Issue 212 (April 2022) - Voci, Davide; Fedeli, Ugo; Farmakis, Ioannis T.; Hobohm, Lukas; Keller, Karsten; Valerio, Luca; Schievano, Elena; Barbiellini Amidei, Claudio; Konstantinides, Stavros V.; Kucher, Nils; Barco, Stefano
Abstract: Background: Pulmonary embolism is a known complication of coronavirus disease 2019 (COVID-19). Epidemiological population data focusing on pulmonary embolism-related mortality is limited. Methods: Veneto is a region in Northern Italy counting 4, 879, 133 inhabitants in 2020. All ICD-10 codes from death certificates (1st January 2018 to 31st December 2020) were examined. Comparisons were made between 2020 (COVID-19 outbreak) and the average of the two-year period 2018–2019. All-cause, COVID-19-related and the following cardiovascular deaths have been studied: pulmonary embolism, hypertensive disease, ischemic heart disease, atrial fibrillation/flutter, and cerebrovascular diseases. Results: In 2020, a total of 56, 412 deaths were recorded, corresponding to a 16% ( n  = 7806) increase compared to the period 2018–2019. The relative percentage increase during the so-called first and second waves was 19% and 44%, respectively. Of 7806 excess deaths, COVID-19 codes were reported in 90% of death certificates. The percentage increase in pulmonary embolism-related deaths was 27% (95%CI 19–35%), 1018 deaths during the year 2020, compared to 804 mean annual deaths in the period 2018–2019. This was more evident among men, who experience an absolute increase of 147 deaths (+45%), than in women (+67 deaths; +14%). The increase was primarily driven by deaths recorded during the second wave (+91% in October–December). An excess of deaths, particularly among men and during the second wave, was also observed for other cardiovascular diseases, notably hypertensive disease, atrial fibrillation, cerebrovascular disease, and ischemic heart disease. Conclusions: We observed a considerable increase of all-cause mortality during the year 2020. This was mainly driven by COVID-19 and its complications. The relative increase in the number of pulmonary embolism-related deaths was more prominent during the second wave, suggesting a possible underdiagnosis during the first wave. Highlights: In 2020, 56, 412 deaths occurred in the Veneto region (Northern Italy), corresponding to a 16%-increase vs. 2018–2019. COVID-19 codes were reported in 90% of overall excess deaths registered in 2020. The increase in pulmonary embolism-related deaths was 27% (95%CI 19–35%). This increase was greater in men (+45% vs. +14% in women), and in the second wave (+91%).